استخدام المفردات العربية المقترضة في اللغة الإندونيسية - Nasrullah, Yufi Mohammad (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2017)
This research is aiming at analyzing the use of Arabic loan words in Indonesian language and conducting contrastive analysis between the two languages for the purpose of making teaching materials. To this end, the researcher used descriptive, analytic, and survey-based method. In so doing, the researcher identifies, classifies, and describes all that related to Arabic loan words in Indonesian language. The researcher then analyzes them in terms of phonetic, morphology, and semantic. Likewise, the researcher uses contrastive method to analyze the differences between Arabic and Indonesian language in all linguistic levels and to predict difficulties that Indonesian students might face in learning Arabic. This research concludes that Arabic loan words in Indonesian language make learning Arabic easier for Indonesian students. Accordingly, Arabic loan words should be considered in devising Arabic learning materials. It also discovers that the best method to make Arabic learning materials for Indonesian students should be based on scientific processes, that is by devising Arabic teaching materials which is purposely designed for non-Arabic speakers. Similarly, the contrastive method also ends up in conclusion that the employment of Arabic loan words makes Arabic learning processes easier. This research recommends the use of Arabic loan words available in Indonesian language when designing learning materials. By doing so, students can easily make linguistic associations and finally understand learning subjects with easy.